2015
DOI: 10.1007/s10120-015-0516-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic versus open gastrectomy for advanced gastric cancer: an updated meta-analysis

Abstract: Background Laparoscopic gastrectomy (LG) has been used as an alternative to open gastrectomy (OG) to treat early gastric cancer. However, the use of LG for advanced gastric cancer (AGC) has been in debate. Methods Literature retrieval was performed by searching PubMed, EMBASE, and the Cochrane library up to July 2014. Potential studies comparing the surgical effects between LG with OG were evaluated and data were extracted accordingly. Meta-analysis was carried out using RevMan. The pooled risk ratio and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 112 publications
(64 reference statements)
9
47
1
2
Order By: Relevance
“…Laparoscopic surgery has the potential benefit of decreased postoperative morbidity and reduced recovery time. Although concerns existed regarding the possibility of a reduced nodal harvest with a laparoscopic approach, a recent meta-analysis suggests that lymph node yields are comparable for both approaches [30]. Trials from the Far East have reported equivalent results to open surgery for distal gastrectomy, but there remain some technical issues particularly for anastomosis for total gastrectomy [31,32].…”
Section: Resectable Gastric Cancer [Iii B] Multidisciplinary Treatmmentioning
confidence: 99%
“…Laparoscopic surgery has the potential benefit of decreased postoperative morbidity and reduced recovery time. Although concerns existed regarding the possibility of a reduced nodal harvest with a laparoscopic approach, a recent meta-analysis suggests that lymph node yields are comparable for both approaches [30]. Trials from the Far East have reported equivalent results to open surgery for distal gastrectomy, but there remain some technical issues particularly for anastomosis for total gastrectomy [31,32].…”
Section: Resectable Gastric Cancer [Iii B] Multidisciplinary Treatmmentioning
confidence: 99%
“…Nine meta-analyses compared the outcomes of LG versus OG [12, 13, 17, 26, 27, 29, 34, 38, 45]. There were 2, 5, and 3 meta-analyses comparing the 1-, 3-, 5-year survival, respectively [13, 17, 26, 27, 34].…”
Section: Resultsmentioning
confidence: 99%
“…There were 2, 5, and 3 meta-analyses comparing the 1-, 3-, 5-year survival, respectively [13, 17, 26, 27, 34]. Another two meta-analyses reported the overall survival (OS) without detailed time points [29, 45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 At our institution, a laparoscopic gastrectomy is performed only in patients with early gastric cancer, and accumulation of results in enough patients is not yet available for analysis. Therefore, the present study focused on patients with gastric cancer who underwent open gastrectomy.…”
mentioning
confidence: 99%